1994
DOI: 10.1002/aja.1002000407
|View full text |Cite
|
Sign up to set email alerts
|

Elastic extracellular matrix of the embryonic chick heart: An immunohistological study using laser confocal microscopy

Abstract: The "elastic matrix" constitutes a specialized component of the extracellular matrix which confers resiliency to tissues and organs subjected to repeated deformations. The role of the elastic matrix in living organisms appears to be of key importance since diseases characterized by expression of defective inherited genes which encode components of the elastic matrix lead to premature death. While the elastic matrix of adult organs has received a great deal of attention, little is known about when it first appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 44 publications
1
39
1
Order By: Relevance
“…ELN was previously identified in the E12 myocardium and E14 epicardium, subendocardium, and blood vessels of the embryonic chick heart, while we did not detect ELN during these stages. 72 In assessing our results, perhaps, the increase in ELN at E16.5 is necessary for providing the elasticity for heart recoil as the heart is required to exert more ejection force with an increasing size of the heart and fetal circulation. Soon after birth, the relative decrease in ELN may be the result of, or the stimulus for, complete maturation of cardiomyocytes and corresponding maturation of functional sarcomeres.…”
Section: Discussionmentioning
confidence: 79%
“…ELN was previously identified in the E12 myocardium and E14 epicardium, subendocardium, and blood vessels of the embryonic chick heart, while we did not detect ELN during these stages. 72 In assessing our results, perhaps, the increase in ELN at E16.5 is necessary for providing the elasticity for heart recoil as the heart is required to exert more ejection force with an increasing size of the heart and fetal circulation. Soon after birth, the relative decrease in ELN may be the result of, or the stimulus for, complete maturation of cardiomyocytes and corresponding maturation of functional sarcomeres.…”
Section: Discussionmentioning
confidence: 79%
“…This subepicardium is a hydrated ECM, rich in proteins, including collagens I, IV, V, and VI and fibronectin (Tidball, 1992;Hurlé et al, 1994;Ká lmá n et al, 1995;Bouchey et al, 1996;Kim et al, 1999), flectin (Tsuda et al, 1998), fibulin-2 (Tsuda et al, 2001), GP68 (Morita et al, 1998), laminin and proteoglycans (Ká lmá n et al, 1995), vitronectin, fibrillin-2, elastin (Bouchey et al, 1996), and tenascin-X (Burch et al, 1995). It has been shown that both the epicardium and myocardium contribute proteins to this matrix (Bouchey et al, 1996).…”
Section: The Subepicardial Extracellular Environmentmentioning
confidence: 99%
“…Furthermore, fibronectin has been implied in the migration of endocardial cushion tissue cells (Mjaatvedt et al, 1987;ffrench-Constant and Hynes, 1988;Icardo et al, 19921, and molecules such as fibrillin, emilin (Hurle et al, 1994) and other, yet uncharacterized, extracellular matrix components (Mjaatvedt et al, 1991) could also be involved.…”
Section: A6a In the Developing Heartmentioning
confidence: 99%